Evolution of models of interaction between the state and civil society in Ukraine: from «participatory governance» to «co-creation» - Kozlov, Kostiantyn; Sobol, Roman (Theory and Practice of Public Administration, 2026)
The article examines the evolution of conceptual models of interaction between the state and civil society in Ukraine through the prism of the transition from «participatory governance» to «co-creation» as a new paradigm of public administration. The hypothesis of the study is that this transition reflects not just a change in the terminological apparatus, but a fundamental transformation of the roles of the state, civil society and the individual citizen in the process of making and implementing public decisions, and that Ukraine, as a result of three key shocks – the Revolution of Dignity, decentralization reform and full-scale Russian invasion – has undergone an accelerated trajectory of this transformation, which in other countries lasted for decades. The study uses comparative-analytical and institutional approaches. Based on the systematization of theoretical concepts of New Public Governance (NPG), collaborative governance and co-creation, the key differences between the models are identified and the logic of their sequential deployment in Ukrainian institutional practice is outlined. Particular attention is paid to the analysis of three time horizons: pre-Maidan (before 2014), post-Maidan (2014–2022) and military (from 2022 to the present). It is shown that each of these horizons formed a specific configuration of interaction between public authorities and civil structures – from paternalistic-declarative to participatory-network and, ultimately, to co-creative. The role of digitalization of public administration, in particular the «Diya» platform, in the formation of new forms of civic participation and joint production of public services is established. The challenges facing Ukraine on the path to full-fledged institutionalization of “co-creation” are analyzed: asymmetry of resources between state and civil actors, legal lack of regulation of co-creation mechanisms, risks of co-optation of civil society by the state. It is concluded that “co-creation” in conditions of martial law acquires an additional dimension – a mechanism for preserving and strengthening social resilience, and post-war recovery requires purposeful formation of the institutional architecture of co-creation as a new social contract between the state and citizens. Four strategic tasks for the institutionalization of “co-creation” in Ukraine are identified: normative consolidation, resource symmetry, development of collaborative culture and ensuring democratic quality.